Nup358 integrates nuclear envelope breakdown with kinetochore assembly - Salina, Davide (The Rockefeller University Press, 2003)
Nuclear envelope breakdown (NEBD) and release of condensed chromosomes into the cytoplasm are key events in the early stages of mitosis in metazoans. NEBD involves the disassembly of all major structural elements of the nuclear envelope, including nuclear pore complexes (NPCs), and the dispersal of nuclear membrane components. The breakdown process is facilitated by microtubules of the mitotic spindle. After NEBD, engagement of spindle microtubules with chromosome-associated kinetochores leads to chromatid segregation. Several NPC subunits relocate to kinetochores after NEBD. siRNA-mediated depletion of one of these proteins, Nup358, reveals that it is essential for kinetochore function. In the absence of Nup358, chromosome congression and segregation are severely perturbed. At the same time, the assembly of other kinetochore components is strongly inhibited, leading to aberrant kinetochore structure. The implication is that Nup358 plays an essential role in integrating NEBD with kinetochore maturation and function. Mitotic arrest associated with Nup358 depletion further suggests that mitotic checkpoint complexes may remain active at nonkinetochore sites.